Assessment and Early Identification of Young Children with Social Emotional Difficulties and Behavioral Challenges - Steed, Elizabeth A. Steed A.; Banerjee, Rashida (Journal of Intellectual Disability - Diagnosis and Treatment, 2016)
This paper discusses the issues and challenges to the assessment and early identification of social emotional and behavioral issues in young children birth through five years of age in the United States. The linked system framework of social emotional assessment and intervention [1] is outlined, and recommendations for authentic assessment of social emotional development are provided to assist professionals in identifying young children early for amelioration and prevention of behavioral challenges.